Inside Back Cover Image, Volume 41, Issue 3. Issue 3 (13th April 2021) - Vatansever, Sezen; Schlessinger, Avner; Wacker, Daniel; Kaniskan, H. Ümit; Jin, Jian; Zhou, Ming‐Ming; Zhang, Bin
Abstract : The cover image is based on the Review Article Artificial intelligence and machine learning-aided drug discovery in central nervous system diseases: State‐of‐the‐arts and future directions by Sezen Vatansever et al., https://doi.org/10.1002/med.21764 .